Symbiotic Evolution and Simulation of Motorized and Nonmotorized Vehicles at Right-Turns - Zhixiu Liu; Yi Zeng; Yinwei Zhao (Journal of Advanced Transportation)
This paper constructs a dynamic crossing model for motorized and nonmotorized vehicles at right-turn intersections based on the Lotka–Volterra framework. The study explores equilibrium points and stability conditions within the symbiotic evolution model. By incorporating the Allee effect, the model simulates various stability scenarios and proposes strategies for optimizing the symbiotic evolution of motorized and nonmotorized vehicles. The findings reveal that the evolutionary trends of the interaction system align closely with the predicted trajectories of the proposed model. The stability of the symbiotic evolution model is influenced by the threshold of the Allee effect, initial crossing scales, and the cooperation and suppression coefficients between motorized and nonmotorized vehicles. These insights not only provide a novel perspective for understanding the interaction dynamics of motorized and nonmotorized vehicles but also offer theoretical guidance for improving safety and efficiency at right-turn intersections.